2018
DOI: 10.1002/pon.4744
|View full text |Cite
|
Sign up to set email alerts
|

Risk for use of antidepressants, anxiolytics, and hypnotics in partners of glioma patients—A nationwide study covering 19 years of prescriptions

Abstract: We have documented, for the first time, that the psychological impact of a diagnosis of glioma is such a severe stress exposure that it increases the risk for having medication prescribed to treat symptoms of anxiety, sleep problems, and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…As the most prevalent cancer in the central nervous system because of the noticeable incidence rate, fast relapse and limited survival , gliomas are characterized by persistent growth, reinforced migration and invasion, and multiple molecular and cytogenetic aberrances . Standard glioma therapy consists of surgery before radiotherapy and chemotherapy .…”
mentioning
confidence: 99%
“…As the most prevalent cancer in the central nervous system because of the noticeable incidence rate, fast relapse and limited survival , gliomas are characterized by persistent growth, reinforced migration and invasion, and multiple molecular and cytogenetic aberrances . Standard glioma therapy consists of surgery before radiotherapy and chemotherapy .…”
mentioning
confidence: 99%
“…Second, due to the registry-based design, partners could not be followed after a change in cohabitation, including death of their cohabiting partner. It is plausible that women may face a higher risk of depression after change of cohabitation status, be it due to their partner's death or for other reasons [48]. Third, the analysis of partners had a lower statistical power than in the male cohort (91,881 vs. 351,263 personyears overall).…”
Section: Discussionmentioning
confidence: 98%
“…In a Danish population, the prevalence of moderate‐to‐severe depressive symptoms was five times higher among patients with glioma compared with cancer‐free individuals [19]. Jansson et al also found that partners of patients diagnosed with glioma have a four‐fold higher risk of a first prescription for psychotropic medications within the first year of diagnosis [20]. Caregivers describe healthcare professionals as rarely or never inviting them to discuss their caregiving role; hence, they have limited opportunities to talk about challenges in everyday life [21].…”
Section: Introductionmentioning
confidence: 99%